Has Spectral-Domain Optical Coherence Tomography Retinal Nerve Fiber Layer Assessment Become the Method of Choice for Glaucoma Evaluation in Clinical Practice? - Undrakonda, Vivekanand (Middle East Afr J Ophthalmol, 2019)
AIM: The aim of the study was to assess the role of spectral-domain optical coherence tomography (SD-OCT) as a method of choice for early glaucoma diagnosis in glaucoma suspects. DESIGN: This was a retrospective cross-sectional study. MATERIALS AND METHODS: After a comprehensive ophthalmic examination and visual field analysis, 20 patients were included in each of the three groups: Normal group, possible glaucoma, definitive glaucoma, respectively. The optic nerve head (ONH) and peripapillary retinal nerve fiber layer parameters of participants were analyzed using SD-OCT optic disc cube protocol scans. Data was analyzed using one.way analysis of variance test. RESULTS: ONH RNFL defects in possible glaucoma patients were frequently found in superior, inferior, and temporal quadrants. CONCLUSION: Diagnostic capability of SD-OCT parameters for detection of structural changes in the ONH and retinal nerve fiber layer differed in three groups significantly. Hence, using SD-OCT has become an imperative and quick way of timely diagnosis of glaucoma in private practice.